USING QUESTION GENERATING TECHNIQUE IN TEACHING READING COMPREHENSION FOR THE THIRD SEMESTER STUDENTS AT ENGLISH STUDY PROGRAM OF MUHAMMADIYAH UNIVERSITY OF BENGKULU - Washlurachim Safitri (Premise: Journal of English Education and Applied Linguistics, 2016)
The objective of this research was to find out Using Question Generating Technique Toward Students Reading Comprehension At The Third Semester Students At English Study Program Of Muhammadiyah University Of Bengkulu. The design of this research was Quasi experimental research. The subject of this research is students at the third semester of English study program. They were A class  that consist of 20 students and D class that consist of 20 students. In collecting data, the researcher used some steps; firstly the students were given a pre-test before the researcher applied Question Generating Technique. Then, the researcher did the treatment for three meetings to the experimental class, after that the researcher did post test to both classes. The last, the researcher analyzed the result of reading test by using criteria for the assessment. The final step was the researcher discussed and concluded the data. The result of this research showed that the tobt was  4,880. Whereas, the degree of freedom of post-test is 68, means that the ttable was 2.021. Based on the scores gained, it shows that tobt is higher than ttable (9,911>4,880). There is a significant difference between the post-test mean of the experimental and control class. The result also showed that the students’ comprehension in reading was significantly. In conclusion, the Question Generating Technique had been successfully gave positive effect to the students’ reading comprehension particularly in reading subject in English study program of University Muhammadiyah of Bengkulu.